Partitioning of Environmental and Taxonomic Controls on Brazilian Foliar Content of Carbon and Nitrogen and Stable Isotopes - Martinelli, Luiz A.; Abdalla-Filho, Adibe L.; Gomes, Taciana F.; Lins, Silvia R. M.; Mariano, Eduardo; Soltangheisi, Amin; de Camargo, Plinio B.; Vieira, Simone A.; Higuchi, Niro; Nardoto, Gabriela B. (Frontiers in Forests and Global Change, 2021)
The Neotropics harbor some of the most diversified woody species in the world, and to understand the nutrient dynamics in these ecosystems, it is crucial to understand the role of plant taxonomy. In addition, biological nitrogen (N) fixation (BNF) in the tropics is one of the key processes affecting the global N cycle. Our objective was to (i) investigate the role of taxonomy and sampling site as predictors of foliar carbon (C) and N concentration and its stable isotopes (i.e., δ13C and δ15N); (ii) assess differences in foliar N, C:N ratio, and δ15N among three functional groups: species of N2-fixers and non-fixers of the Fabaceae family, as well as non-Fabaceae species; and (iii) examine the effect of wood density on tree foliar properties. We hypothesized that Fabaceae specimens in symbiosis with N2-fixers would possess a higher foliar N than non-fixing plants, including those of the Fabaceae family, as well as high-density trees would have higher foliar C and C:N ratio relative to low-density trees, where the latter invest in nutrients instead of structural C. We used a data set composed of 3,668 specimens sampled in three main biomes of Brazil: Amazon, Atlantic Forest, and Cerrado. The partitioning of variance had a higher influence of taxonomy on leaf C, N, and C:N ratio. Conversely, foliar δ13C and δ15N were environmentally constrained. While family was the most important taxonomy level for C, N, and C:N ratio, species played a major role for δ13C and δ15N. Foliar N followed the pattern fixers > non-fixers > non-Fabaceae, while C:N ratio had an opposite trend. In addition, foliar C was correlated with wood density, where high-density > medium-density and low-density woods. The large variability of δ15N was observed among Fabaceae species, demonstrates the complexity of using δ15N as an indicator of BNF. The higher foliar N of Fabaceae non-fixers than non-Fabaceae specimens support the hypothesis that an N-demanding lifestyle is an inherent pattern in this family. Lastly, although observed in some studies, the prediction of foliar properties using wood density is challenging, and future research on this topic is needed.